THE INFLUENCE OF HUMIDITY, TEMPERATURE, AND VENTILATION AREA ON THE INCIDENCE OF TUBERCULOSIS AMONG FARMERS IN INDONESIA: A CASE CONTROL STUDY - Adha , Aziza Zahrotul; Kinanthi, Citra Anggun (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Tuberculosis is transmitted through infected droplets. Ponorogo Regency is ranked 8th in TB mortality rates in East Java. The highest TB cases in Ponorogo Regency are in the Kauman Community Health Center and most people with pulmonary TB work as farmers. Purpose: The aim of the research was to analyze the effect of humidity, temperature, and ventilation area on the incidence of pulmonary TB in farmers in the working area of Kauman Health Center, Ponorogo Regency. Methods: The research design is analytical observational with a case control approach. The number of research samples was 39 cases and 39 controls. The sampling technique uses simple random sampling. The research data sources are primary data and secondary data with measurement techniques. The dependent variable in this study is the incidence of pulmonary TB in farmers. Meanwhile, the independent variables are humidity, temperature, and ventilation area. Data analysis uses univariate and bivariate analysis using logistic regression tests. Results: Most respondents have houses with humidity levels that do not meet the requirements (59%), room temperatures that do not meet the requirements (79.5%), and ventilation areas that do not meet the requirements (73.5%). There is a significant influence between humidity (p value 0.007; OR=3.753), temperature (p value 0.032; OR=3.889), and ventilation area (p value 0.025; OR=3.437) on the incidence of pulmonary TB in farmers. Conclusion: There is a significant influence between humidity, temperature, and ventilation area on the incidence of pulmonary TB in farmers.